2014
DOI: 10.1021/jm500024v
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Cytotoxic Ortho-Aryl Chalcones as New Scaffold Targeting Tubulin and Mitosis with Affinity-Based Fluorescence

Abstract: A series of new ortho-aryl chalcones have been designed and synthesized. Many of these compounds were found to exhibit significant antiproliferation activity toward a panel of cancer cell lines. Selected compounds show potent cytotoxicity against several drug resistant cell lines including paclitaxel (Taxol) resistant human ovarian carcinoma cells, vincristine resistant human ileocecum carcinoma cells, and doxorubicin resistant human breast carcinoma cells. Further investigation revealed that active analogues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…This potential binding site is consistent with several other literature reports. For instance, docking studies suggested that cytotoxic chalcones fit well in the colchicine binding site, and colchicine was shown to compete with cytotoxic chalcones for tubulin binding . Such a potential binding site is also consistent with the fact that C95 labeled α‐tubulin as well, which indicated that C95 may bind around the interface of the α‐tubulin and β‐tubulin heterodimer.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…This potential binding site is consistent with several other literature reports. For instance, docking studies suggested that cytotoxic chalcones fit well in the colchicine binding site, and colchicine was shown to compete with cytotoxic chalcones for tubulin binding . Such a potential binding site is also consistent with the fact that C95 labeled α‐tubulin as well, which indicated that C95 may bind around the interface of the α‐tubulin and β‐tubulin heterodimer.…”
Section: Resultsmentioning
confidence: 70%
“…Moreover, there has been little evidence to support any direct interactions of cytotoxic chalcones with these putative targets in intact cells. Taking tubulin as an example, although chalcone‐based compounds have been documented to inhibit tubulin polymerization ex vitro, their direct interaction in cells remains to be validated. Similarly, whereas cells upon cytotoxic chalcone exposure would lose microtubule structure, such an effect can be mediated by multiple mechanisms .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, compound 36 and similar analogues were found to exhibit affinity-induced fluorescence during tubulin-binding. 78 Also within chalcones, the B-ring can accommodate indol rings, as exemplified by 37 (IPP51) 79 that inhibited tumor growth in a human bladder xenograft model. Other examples where the bridge connecting rings A and B contains a pyridine have been described by Zheng et al 80 2.4.2.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…13 Chalcones, the precursors of flavonoids and isoflavonoids, are abundant in edible plants, and have also been shown to display a diverse array of pharmacological activities. 16 With millepachine, a chalcone analogue isolated from the Millettia pachycarpa as the model, Chen synthesized and evaluated twenty one dirivatives for their antiproliferative activity and the optimal compound was considered as promising anticancer agent. For example, Ducki incorporated the aryl substitution pattern of CA4 into chalcones and found that some of these compounds exhibited good antimitotic properties.…”
Section: Introductionmentioning
confidence: 99%